The Impact of Exposure to Blood Lead Levels on Online Ojek Driver Students on Intelligence and Communication Anxiety - Indah Tri Susilowati; Noviana Dewi; Stefanus Khrismasagung Trikusumaadi; Dita Nova Saputri (Indonesian Journal of Global Health Research, 2022)
Motor vehicle smoke pollution contains lead exposure which if accumulated in the blood exceeds the stipulated level, it can cause health problems, both psychological and physical. This study aims to determine the effect of exposure to lead emitted by motor vehicle fumes on students who take part-time jobs as online motorcycle taxi drivers. The influences studied include IQ levels and communication anxiety. Measurement of IQ using the WAIS test (Wechsler Adult Intelligence Scale) while Communication Anxiety was measured using the Communication Anxiety Scale. Blood lead levels were checked using the GFAAS tool. The data on blood lead levels, IQ scores and communication anxiety were then tested for normality using the Kolmogorov Smirnov technique and followed by a linearity test with a test of linearity. Then for hypothesis testing, the data were analyzed using simple regression analysis. The result is that there is a relationship between blood lead levels with IQ levels and communication anxiety.